DESAIN E-MODUL FLIPBOOK BERBASIS CULTURALLY RESPONSIVE TEACHING (CRT) PADA MATERI TRANSFORMASI GEOMETRI DI SEKOLAH MENENGAH KEJURUAN - Achmad Buchori; Lukman Harun (LPPM Universitas Bina Bangsa, 2020)
Using digital technology is an effective way to improve the quality of learning. One of the digital technologies that can be used in learning is the Flipbook E-Module. This study aims to design an e-module that is following the cultural characteristics of students and the mathematics material in the Class XI SMK Curriculum 2013, namely geometric transformation. This research uses the ADDIE R&D model (Analysis, Design, Develop, Implement, and Evaluate), which only includes three steps due to time constraints in product creation and validation. The results of e-module flipbooks based on Culturally Responsive Teaching (CRT) on geometry transformation materials equipped with the use of GeoGebra as an innovative use of teaching materials following technological developments. Based on the validation by media experts and material experts on the e-module flipbook on geometry transformation material, scores of 90,7 and 90,3 were obtained, indicating that the e-module was very feasible to use in learning transformation geometry.